Can rotations improve management of herbicide-resistant annual sowthistle (Sonchus oleraceus) and prickly lettuce (Lactuca serriola) in lentil production systems of southern Australia?. (9th August 2021) - Merriam, Alicia B.; Malone, Jenna; Gill, Gurjeet; Preston, Christopher
Abstract: In southern Australia, annual sowthistle and prickly lettuce have become more prevalent following the adoption of reduced tillage cropping systems. They are especially problematic in lentil and other pulse crops, which are weakly competitive and have few herbicide options available for POST control of broadleaf weeds. This study aimed to evaluate the influence of management in a previous cereal crop on weed densities in a subsequent crop. At two field sites, crop seeding density and POST herbicide treatments (a conventional choice that included metsulfuron-methyl and MCPA; and a proactive choice that included bromoxynil, picolinafen, and MCPA) were applied to a wheat crop, and weed density was assessed at the beginning of the following season to measure for a legacy effect of the treatments. Study site populations were also screened for herbicide resistance and were found to have high (≥90% survival) ALS inhibitor resistance. Crop competition treatments had no effect on weed populations, and effects of herbicide treatment were significant at only one of the sites. At this site, both herbicide treatments had lower weed densities than the nontreated in the first year, but the legacy effect was only significant for annual sowthistle density in the proactive treatment. At both sites, even where weeds were extremely sparse or completely controlled following herbicide treatment in the first year, moderate densities were observed the following year, indicating that colonization from the seedbank or adjacent areas could be contributing to weed numbers. Weed density assessments and accurate knowledge of the herbicide resistance status of target weeds should guide herbicide selection to maximize control.